Impact of vitamin D receptor gene polymorphisms on blood lead levels in Thai lead exposed workers - Winai Wananukul (2018)
Background: Although lead poisoning has aroused public concern, its toxicokinetics and mechanism of toxicity are still unclear. Vitamin D regulates calcium homeostasis via vitamin D receptor (VDR) and its polymorphisms cause variability of body calcium and bone density. VDR polymorphisms may correlate with the variability of body burden of lead. Objective: Determine if vitamin D receptor polymorphisms is associated with blood lead in Thai workers exposed to lead. Subjects and methods: Four hundred fifteen lead exposure workers were recruited in the study. Blood lead level was determined as a biomarker of lead. Five VDR polymorphisms (FokI, BsmI, Apa, TagI, and Cdx2) were studied. Results: The allele frequencies of F/f, B/b, A/a, T/t, and A/G for FokI, BsamI, ApaI, TagI and Cdx-2 polymorphisms were 059/0.41, 0.07/0.93, 0.32/0.68, 0.94/0.06 and 0.4/0.6, respectively. Gender, smoking status, lead exposure status, BsmI, and TaqI polymorphisms were associated with blood lead level. The BB genotype of BsmI and the tt genotype of TaqI have significantly lower blood lead levels than other genotypes of their polymorphisms. Conclusion: The BsmI and TaqI polymorphisms of the vitamin D receptor gene had impact on the blood lead level. This association was similar to their effects on calcium. Lead might share the same toxicokinetics with calcium.